The role of therapy productiveness on MFT clients' intentions to persist in therapy. Issue 1 (1st January 2019) - D'Aniello, Carissa; Tambling, Rachel
Abstract: Many clients drop out of therapy before reaching their goals (Bohart & Wade, 2013 ), though being in therapy produces more change than not being in therapy (Lambert, 1992 ). To investigate the factors that affect clients' decisions to persist in therapy, we surveyed a convenience sample of 72 clients of MFTs in individual, couple or family therapy currently in treatment in a community-based therapy center. We tested moderation using regression analysis to determine the extent to which productiveness moderates the relationship between therapeutic alliance and intended persistence. Results showed that productiveness moderated the relationship between therapeutic alliance and intended persistence. Specifically, higher levels of therapy productiveness strengthened the relationship between therapeutic alliance and therapy persistence. Implications for future research and practice are presented and discussed.